1974
DOI: 10.1007/bf01965226
|View full text |Cite
|
Sign up to set email alerts
|

Blood platelets and the inflammatory process

Abstract: There appears to be an encouraging body of evidence supporting a relationship between hemostasis and inflammation with the platelet being the main link between the two.These processes are both triggered by damage to blood vessels and a response which occurs within seconds of this damage is the adhesion of platelets to the injured tissue and to each other. During the hemostatic process inflammatory agents are released from platelets.Some anti-inflammatory agents such as aspirin also have anti-hemostatie propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The elucidation of the pattern of reactions that constitute the different phases of the inflammatory response has shown that in many points these reactions are similar to those occurring during platelet aggregation [1][2][3]. One of the important questions is, whether platelets play a role in the early phases of the inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The elucidation of the pattern of reactions that constitute the different phases of the inflammatory response has shown that in many points these reactions are similar to those occurring during platelet aggregation [1][2][3]. One of the important questions is, whether platelets play a role in the early phases of the inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the present work, the predictive value of an inhibition of platelet PG synthesis for anti-inflammatory activity is questionable. The involvement of platelets in the inflammatory process especially as a source of PG synthetase, has been considered by SILVER et al [10] and VINCENT et al [11]. Our results suggest that an inhibition of platelet function, although not necessarily via an inhibition of platelet PG synthesis, may bear a relationship to anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 48%
“…Important reactions are induced through their interference with the activation cascade of the complement [14,19], the kinin [2] and the fibrinolytic [9] system.…”
Section: Diseussionmentioning
confidence: 99%